Debt Relief for Low-Income Countries : The HPIC initiative (Revised '99). (Pamphlet Series, 1999)
This paper analyzes the IMF's Enhanced Initiative for Heavily Indebted Poor Countries, which provides debt relief for low-income countries. The paper highlights that countries affected by the debt crisis of the 1980s received concerted support from the international financial community in the form of Paris Club flow reschedulings, stock-of-debt operations under the Brady plan, and adjustment programs supported by the multilateral financial institutions. These measures proved effective in significantly improving the debt situation of many middle-income countries.